Społeczności lokalne w działaniach na rzecz ochrony środowiska i zrównoważonego rozwoju - Ligia Tuszyńska; Adam Kowalak (Studia Ecologiae et Bioethicae)
The results of the surveys and interviews carried out in the communes of Pomeranian district indicate a great need for coordination of educational actions directed not only for schools, but also for the local communities, there is a necessity for the communes to formulate a programme of environmental education for society that include local circumstances, the level of both knowlegde and awareness of society in the field of environmental protection, biodiversity and sustainable development are still unsufficient and apart from the scholl, they also require the activities of the family and local institutions.